Development of abdominal MRI at 7 Tesla - Doran, Emma (2020)
This thesis covers the development of abdominal magnetic resonance imaging (MRI) at the ultra-high field (UHF) of 7 Tesla (7 T). The advantages and challenges of MR imaging at 7 T are introduced alongside an overview of a parallel transmit system and its associated applications. Methods for mapping the B1+ field are outlined with a focus on the further adaptations required to obtain accurate measurements at UHF.